Acquisition of Technological Capability by Firms in the Aerospace Cluster of Bengaluru - Chandra N, Sharath; Raghavendra, N V; Shekar, G L; Khan, P. Mueen Ahamadulla (The Asian Journal of Technology Management (AJTM), 2019)
Abstract. Technological capability is believed to be the ability of a firm to make innovations in its products and manufacturing processes. It is especially important for SMEs to make informed choices of technology to meet global quality standards and adopt the best practices to ensure productivity. The acquisition of technological capability takes place through deliberate efforts by firms, which is characterised as technological learning mechanisms in the literature. This paper provides an assessment of influence of technological learning mechanisms on the acquisition of technological capability of SMEs in the Bengaluru aerospace cluster in south India. Firstly, a measure is developed to quantify technological capability at firm level. Seventeen variables, which form the building blocks have been factored into four factors in order to develop the measure called Technology Index (TI). Secondly, learning variables, which significantly influence technological capability have been identified through regression analysis. Learning variables education of CEO, years of operation in aerospace industry and vertical collaboration have been found to significantly influence technological capability of firms. This analyses lead to important lessons both for entrepreneurs and policy makers.Keywords: Technological capability, technology index, aerospace cluster, learning variables, technology measurement.